Navigating Institutional Complexity: The Production of Risk Culture in the Financial Sector - Palermo, Tommaso; Power, Michael; Ashby, Simon (Journal of Management Studies, 2017)
Following the financial crisis, financial sector organizations faced increased pressures to reform their ‘risk cultures’. In this paper, we argue that the emergence of regulatory and managerial attention to risk culture is symptomatic of pressures to redefine the fundamental ends of financial institutions and to rebalance the pre‐crisis emphasis on a logic of opportunity and risk‐taking with a logic of precaution and risk control. Based on the analysis of normative practitioner texts and on extended contact with regulators, advisers and corporate actors in the UK financial sector over four years, we show how this initial complexity of ends is translated into uncertainty and conflict about the means through which risk culture might become an object amenable to intervention. On this basis, we contribute to the growing literature on ‘institutional complexity’ by showing how organizational actors address conflicting pressures about both ends and means, and by discussing some key implications of their simplification strategies. Our analysis also contributes to recent studies of ‘means‐ends decoupling’, showing how means, ends and the object of intervention itself – risk culture – co‐evolve as they are reconstructed by organizational actors via their everyday practices.